Penyuluhan Hukum dan Sosialisasi Pembentukan Peraturan Desa di Desa Cimenga Kabupaten Lebak - Ricky Riyadi (Universitas 45 Surabaya, 2025)
Legal education and outreach on the formation of Village Regulations in Cimenga Village, Lebak Regency, aims to increase the understanding of the community and village government regarding the procedures for forming village regulations in accordance with statutory provisions. This activity includes presentation of material regarding the legal bases governing villages, including Minister of Home Affairs Regulation Number 111 of 2014 concerning Technical Guidelines for Village Regulations, as well as other related regulations. This socialization also emphasizes the urgency of forming village regulations that are clear and based on local customs to prevent potential conflict and irregularities in village governance. The methods used in this outreach include lectures, interactive dialogue, and providing feedback through questionnaires to measure the level of participants' understanding. It is hoped that with this activity, the village government and community can better understand the role and importance of forming village regulations that are in accordance with legal principles and local needs.